Utilizing decision tree machine model to map dental students’ preferred learning styles with suitable instructional strategies - Shoaib, Lily Azura; Safii, Syarida Hasnur; Idris, Norisma; Hussin, Ruhaya; Sazali, Muhamad Amin Hakim (Springer Nature, 2024)
Background Growing demand for student-centered learning (SCL) has been observed in higher education settings including dentistry. However, application of SCL in dental education is limited. Hence, this study aimed to facilitate SCL application in dentistry utilising a decision tree machine learning (ML) technique to map dental students’ preferred learning styles (LS) with suitable instructional strategies (IS) as a promising approach to develop an IS recommender tool for dental students.